2000
DOI: 10.1046/j.1439-0426.2000.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative survival and growth of embryos, larvae, and juveniles of pejerrey Odontesthes bonariensis and O. hatcheri * at different salinities

Abstract: Summary The hatching of fertilized eggs and the survival and growth of larvae and juveniles of the inland‐water atherinids Odontesthes bonariensis (Valenciennes 1835) and O. hatcheri (Eigenmann 1909) were examined at salinities of 0, 5, 10, 20, and 30 ppt. In addition, a limited study compared the salinity responses of O. bonariensis eggs and larvae from different origins. Overall, embryos, larvae, and juveniles of both species were euryhaline, although best survival and growth rates were obtained at the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
2
18
0
6
Order By: Relevance
“…The lower cortisol levels at 5 and 20ppt after stress of transport or crowding of adult pejerrey as observed in previous studies (Tsuzuki et al, 2001) were possibly due to a natural preference for higher salinity levels, resulting in decreased cortisol secretion, or increased clearance rates, as pointed out by Goswami et al (1983), Redding et al (1984) and Nichols and Weisbart (1985). Data on the survival and growth of pejerrey larvae and adults at different salinities seemed to support the first hypothesis as both were shown to be euryhaline and to perform better at salinities close to 20ppt, especially compared to 0ppt (Tsuzuki et al, 2000a). This notion was reinforced by information on the natural distribution of this species, which, although continental, coincides with areas where surface and ground water have substantial salinity (Mc Donagh, 1934;Ringuelet et al, 1967;Saravia et al, 1987).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The lower cortisol levels at 5 and 20ppt after stress of transport or crowding of adult pejerrey as observed in previous studies (Tsuzuki et al, 2001) were possibly due to a natural preference for higher salinity levels, resulting in decreased cortisol secretion, or increased clearance rates, as pointed out by Goswami et al (1983), Redding et al (1984) and Nichols and Weisbart (1985). Data on the survival and growth of pejerrey larvae and adults at different salinities seemed to support the first hypothesis as both were shown to be euryhaline and to perform better at salinities close to 20ppt, especially compared to 0ppt (Tsuzuki et al, 2000a). This notion was reinforced by information on the natural distribution of this species, which, although continental, coincides with areas where surface and ground water have substantial salinity (Mc Donagh, 1934;Ringuelet et al, 1967;Saravia et al, 1987).…”
Section: Resultssupporting
confidence: 63%
“…Pejerrey is considered as a freshwater species because of its natural occurrence in inland waters, and introductions domestically and to other countries have been made almost entirely in fresh water. However, recent studies revealed better performance, in particular higher survival and growth rates, at salinities of 5 to 20 parts per thousand (ppt) compared to 0ppt (Tsuzuki et al, 2000a;.…”
Section: Introductionmentioning
confidence: 99%
“…Low water salinity in post-larvae fish farming has less effect on the growth and survival than high salinities, as observed by Specker et al (1999) for Paralichthys dentatus. Several freshwater fish species show maximum growth and survival rates when reared in slightly salinized water, up to 5‰, such as Cyprinus carpio (Lam and Sharma, 1985), Odontethes hatcheri (Tsuzuki et al, 2000), Heterobranchus longifilis (Fashina-Bombata and Busari, 2003), whereas others like Ictalurus punctatus show reduced fingerling growth (Baldisserotto, 2002). In salinities above 1.7‰ reduced growth of pintado may have been caused by the high energy consumption to maintain inverse osmoregulation, i.e., eliminating salt and retaining water.…”
Section: Discussionmentioning
confidence: 99%
“…Both species have a remarkable tolerance to high salinity but not to sea water (Tsuzuki et al 2000;Gómez and Ferriz 2001). Dyer (2000) and Menni (2004) agree in their view that both species were isolated by marine incursions several millions of years ago (Hubert and Renno 2006).…”
Section: Distribution Breeding and Temperaturementioning
confidence: 99%